The trickster in West Africa : a study of mythic irony and sacred delight - Pelton, Robert D. (Hermeneutics, studies in the history of religions., 1989)
The trickster appears in the myths and folktales of nearly every traditional society. Robert Pelton examines Ashanti, Fon, Yoruba, and Dogon trickster-figures in their social and mythical contexts and in light of contemporary thought, exploring the way the trickster links animality and ritual transformation; culture, sex, and laughter; cosmic process and personal history; divination and social change. -- Publisher description from http://www.ucpress.edu (Oct. 3, 2011).